Strong association between cardio-pulmonary exercise parameters and mortality in adults with transposition of the great arteries and a systemic right ventricle. (25th November 2020) - De Santis, J; Constantine, A; Ministeri, M; Kempny, A; Rafiq, I; Barradas-Pires, A; Rybicka, J; Babu-Narayan, S; Gatzoulis, M.A; Dimopoulos, K
Abstract: Introduction: Patients with transposition of the great arteries (TGA) who underwent atrial switch repair (ASR, Senning or Mustard) and patients with congenitally corrected TGA (ccTGA) have a morphological right ventricle in the systemic position. Patient with a systemic right ventricle (SRV) are prone to exercise intolerance and have a significantly worse survival compared to the general population. Risk stratification is an important component of their management and routine clinical assessment. Purpose: To describe the severity and mechanisms of exercise limitation in patients with a SRV, and its relation to mortality. Methods: All SRV patients who underwent a cardiopulmonary exercise test (CPET) in a tertiary centre from 2000–2019 were included. Demographics, clinical and imaging data were collected around the time of CPET. Cox survival analysis was used to assess the association between exercise parameters and mortality. Results: A total of 262 patients underwent at least one CPET during the study period. Mean age at CPET was 37.4±12 and 154 (58.8%) were male. The majority of patients had TGA with ASR (150, 57.3%), while 112 (42.7%) had ccTGA. The majority of patients were in NYHA class I (36%) or II (36%). Moderate or severe right ventricular dysfunction was present in 188 (78.0%), while 59 (26.6%) patients had moderate or severe TR. Baseline oxygen saturation was 96±4% and median BNP was 71 [37–140] ng/L. Co-existent congenital lesions were present in almost one half (48.8%) of patients, including pulmonary stenosis (31, 7, 12.1%) and ventricular septal defect (61, 3, 23.4%). Average peak VO2 (pVO2) was 22.3±8.1ml/kg/min, (66±22% of predicted). The VE/VCO2 slope was raised (>33) in 128 (49%) patients. Patients who were cyanotic at rest and/or desaturated during exercise had a significantly higher VE/VCO2 slope (40.3±15.9 vs. 33.6±9.0, p=0.0004) and lower pVO2 (20.7±8.0 vs. 24.3±7.7, p=0.0007). A total of 119 (46.1%) patients achieved target heart rate, while 36 (14.0%) patients were unable to achieve a heart rate of at least 60% predicted. Over a median follow up of 3.0 [1.1–5.9] years, 36 (13.7%) patients died. Univariable predictors of mortality from CPET included pVO2, VE/VCO2 slope, heart rate reserve (HRR), anaerobic threshold, peak systolic blood pressure and exercise time (Figure). On bivariable analysis using pVO2 with each of the other exercise parameters, only peak systolic blood pressure remained in the model, even when adding age. In ccTGAs, peak VO2 was the only parameter remaining in the multivariable models. In ASR patients, HRR was stronger than all other parameters. Conclusion: In this large cohort of patients with systemic RVs, older than existing reports in this area, peak VO2, peak systolic BP and HRR appear to be stongly related to mortality. These findings reflect the underlying physiology and consequences of previous surgery and should be used in clinical practice to risk stratify patients. Funding Acknowledgement: Type of funding source: None